Social Construction of Islam by the Shi’a Community in Pekalongan City, Central Java - Muhandis Azzuhri; Maskhur Maskhur; Ahmed Abdul Malik; Farah Farhatus Soimah (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2022)
This study intends to identify the establishment of Islamic social construction in the Shi’a community in Pekalongan City. Qualitative research applied in this study gathered from case studies using a phenomenological approach. Data came from in-depth observation, interviews, and documentation. The theory of social construction formulated by Peter L. Berger and Thomas Luckmann became the basic theory of analysis. The results showed that the social construction of Islam in the Shi’a community in Pekalongan City was formed through externalization, objectivization, and internalization. The process of externalization through the dissemination of knowledge of Shi’a teachings, as well as about the specialty of Ahl al-Bayt in the religious authority of Muslims. Objectivization happened according to Shi’a teaching habituation moderately, responding to the plurality of understandings and social attitudes of the Muslim religion. The internalization process went with awareness to not apply the teachings of taqiyyah. In addition, the availability to live in harmony thrives on maintaining the integration of state life in Indonesia. The theoretical implications of this study show that theological inclusivism can form moderate and open religious social understandings and attitudes in the plurality of religious life. However, this study did not examine the role of the Pekalongan City Government in advocating for the benefit of the Shi’a community as a minority group in Pekalongan City which becomes the limitation of this study.